2016
DOI: 10.1016/j.psyneuen.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Panel manipulation in social stress testing: The Bath Experimental Stress Test for Children (BEST-C)

Abstract: SummaryBackground: Whilst acute stress paradigms in adults make use of adult panel members, similar paradigms modified for child participants have not manipulated the panel.Most work has utilised an audience of adult confederates, regardless of the age of the population being tested. The aim of this study was to trial a social stress test for children that provided a meaningful environment using age-matched child peers as panel actors.Methods: Thirty-three participants (7-11 years) underwent the Bath Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 45 publications
2
13
2
Order By: Relevance
“…Responses to the BEST‐C differed between the four prior stress–resilience groups, with children who had previously experienced more stress and had more characteristics of resilience displaying the lowest salivary cortisol responses to the task. There were no statistically significant increases in salivary cortisol in response to the BEST‐C stress testing phase, contrary to previous findings (Cheetham & Turner‐Cobb, ). However, heart rate did increase in response to the task and 31 out of 34 participants self‐reported that they found the task stressful or worrying and were relieved when it was over.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Responses to the BEST‐C differed between the four prior stress–resilience groups, with children who had previously experienced more stress and had more characteristics of resilience displaying the lowest salivary cortisol responses to the task. There were no statistically significant increases in salivary cortisol in response to the BEST‐C stress testing phase, contrary to previous findings (Cheetham & Turner‐Cobb, ). However, heart rate did increase in response to the task and 31 out of 34 participants self‐reported that they found the task stressful or worrying and were relieved when it was over.…”
Section: Discussioncontrasting
confidence: 99%
“…There was an increase in salivary cortisol in anticipation of the task, suggesting the prospect of completing the BEST‐C was stress‐inducing. This anticipation effect is in line with findings regarding anticipation stress (Cheetham & Turner‐Cobb, ). Heightened levels of salivary cortisol during the anticipation period could also explain why salivary cortisol did not increase further during the task as peak salivary cortisol levels may have been reached.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, it is imperative to explore children's early experiences of stress and coping. The importance of interviewing child-parent dyads together has been highlighted as providing the most illuminating and rich data as children and their parents interact to build a narrative (Cheetham & Turner-Cobb, 2016). While questionnaire-assessed life events report the number of major stressors children have encountered, they do not reveal the extent to which the stressors have influenced the child, capturing data on only certain aspects of children's stress experience (Holmes & Rahe, 1967).…”
Section: What Does the Study Add?mentioning
confidence: 99%